1998
DOI: 10.1097/00000539-199810000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Discharge Time in Adult Outpatients

Abstract: The relative importance of anesthetic and nonanesthetic factors were evaluated as determinants of discharge time after ambulatory surgery. Postoperative nursing care was the single most important factor after general anesthesia; anesthetic drugs, anesthetic technique, and prevention of pain and emetic symptoms were of selective importance depending on patient gender and type of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(101 citation statements)
references
References 18 publications
4
95
1
1
Order By: Relevance
“…Previous reports demonstrated that duration and type of surgery are important factors determining the length of stay [3,6,[7][8][9][10]17,18], which is consistent with our study. Our delayed patients used more intraoperative and postoperative analgesics and reported more frequent postdischarge pain.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Previous reports demonstrated that duration and type of surgery are important factors determining the length of stay [3,6,[7][8][9][10]17,18], which is consistent with our study. Our delayed patients used more intraoperative and postoperative analgesics and reported more frequent postdischarge pain.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we have confirmed the previous reports demonstrating that delays in discharge are due to adverse symptoms or social/system problems [3,[6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In addition, we found that delayed discharge was associated with increased postdischarge pain, lower RNA level, and patient's unwillingness to receive same-day surgery again.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations